L’EVALUATION DE LA COMPREHENSION DE L’ECRIT («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses ways to develop and assess reading competence when teaching French as a foreign language.
Keywords: reading, assessment, education, science, thinking.